On four new species of the jumping spider genus Mago O. Pickard-Cambridge, 1882 from South America (Araneae: Salticidae) - Costa, Erika L.s.; Ruiz, Gustavo R.s. (Zootaxa, 2017)
Four new species of Mago O. Pickard-Cambridge, 1882 are described. Mago furcatus sp. nov. and Mago mimicus sp. nov. are described from Ecuador (Orellana and Napo provinces, respectively), both based only on the male holotypes. Both sexes of Mago pardo sp. nov. and the male of Mago apophysis sp. nov. are also described from the state of Pará, Brazil. A map with records of these species is given.